The practice of using evidence in kindergarten: The role of purposeful observation. Issue 8 (24th July 2015) - Monteira, Sabela F.; Jiménez‐Aleixandre, María Pilar
Abstract: This article examines kindergarten children's (5–6 years old) engagement in scientific practices, with a focus on generating and using evidence to support claims, during a 5‐month project about snails. The research questions are as follows: (1) what meanings do kindergarteners construct for what constitutes evidence? How are those meanings reflected in the development of data into evidence? (2) Which ways of gathering empirical evidence are jointly constructed by children and teacher during the project? (3) How do children use evidence to revise their understandings? The participants are one class of Early Childhood Education children ( N  = 25) and their teacher. They were engaged in a project about snails, involving pursuing their own questions, carrying out experiments and purposeful observations, collecting data and drawing conclusions, under the guidance of the teacher. The results show that children developed meanings of a certain level of sophistication about evidence, that they distinguished between empirical evidence from planned experiments and from prolonged observation, which we call purposeful, and that they combined different types of evidence in the revision of their ideas about snails. We identified two levels in the development of data into evidence—closer to descriptive statements and evaluative judgments. We suggest that purposeful observation, which has a clear focus, is guided by the teacher and explicitly discussed, has affordances in early childhood science. For instance, 30 out of 57 evidence statements relate to purposeful observation. Promoting purposeful observation as a source of evidence at this age may allow studying processes both for children (biology processes) and for researchers (learning processes). The results would support Metz's (2011) contention about the relevance of instructional opportunities over developmental constraints. © 2015 Wiley Periodicals, Inc. J Res Sci Teach 53: 1232–1258, 2016